The learning of specific dysfunctional behavioural patterns through social-network and telematics platforms in preadolescents and adolescents. Psychopathological clinical evidence - Giulio Perrotta (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2021)
Purpose: This research addresses the issue of personality profiles of subjects who, due to age and birth in the age of digitalisation and the internet, have been massively exposed to telematic content without extensive parental control. In this research, the subject is addressed to the psychopathological investigation of personalities, according to the PICI-1(TA) model. Methods: Clinical interview and administration of the MMPI-II and PICI-1. Results: The research on a population sample of 975 people demonstrated: 1) On the MMPI-II, they reported 51.8% on the hypochondria clinical scale, 53.2% on the depression scale, 62.2% on the hysteria scale, 66.8% on the schizophrenia scale, 76.7% on the hypomania scale, 82.4% on the psychopathic deviation scale and 83% on the paranoia scale. In relation to the content scales, the matter is different: If for the clinical scales the average is between very close values, for the content scales it is not possible to do so, since the activations in the male group are much lower than in the female group. And in fact: a) for the men's group the following is reported: 52.6% on the depression scale, 64.4% on the cynicism scale, 67.4% on the anger scale, 74% on the antisocial behaviour scale, 76.4% on the social discomfort scale, 84.4% on the family problems scale and 86% on the anxiety scales; b) for the woman's group the following is reported: 85.4% on the social discomfort scale, 86% on the depression scale, 87.7% on the antisocial behaviour scale, 89.5 on the family problems scale, 94.4% on the anxiety and cynicism scales, and 98% on the anger scale. 2) On the PICI-1, the data are even more significant and expressive a precise psychopathological diagnosis of personality. The male population sample of cluster A singularly scored at least 5 dysfunctional traits among bipolar, schizoid and schizoaffective personality disorders, for 84.6% (309/365), thus obtaining a marked diagnosis of specific personality disorder. The remaining sample of the population however obtained individually at least 4 dysfunctional traits among the masochistic, psychopathic, delusional, histrionic, narcissistic and borderline personality disorders. Common diagnoses above 50% include 50.9% (186/365) of paraphiliac disorder, 75.6% (276/365) of sleep-wake disorders and 90.1% (329/365) of behavioural addiction disorders (the largest being 'internet'). The female population sample singularly scored at least 5 dysfunctional traits among borderline, narcissistic and sadistic personality disorders, for 94.7% (578/610), thus obtaining a marked diagnosis of specific personality disorder. The remaining population sample, however, obtained individually at least 4 dysfunctional traits among the bipolar, paranoid, histrionic and psychopathic personality disorders. Common diagnoses above 50% include 50.6% (309/610) of nutrition disorders, 74.9% (457/610) of behavioural addiction disorders (the largest being 'internet') and 92.9% (567/610) of sleep-wake disorders. On the basis of these data, it is reasonable to state that 84.6% (of the selected male population sample) and 94.7% (of the selected male population sample) presents marked psychopathological traits. Specifically: for the male group, the dysfunctional traits refer individually, with at least 5 markings, to bipolar, schizoid, schizoaffective disorder, and with 4, to psychopathic, delusional, narcissistic, histrionic, masochistic and borderline disorder; for the female group, the dysfunctional traits refer individually, with at least 5 markings, to borderline, narcissistic and sadistic disorder, and with 4 markings, to bipolar, paranoid, histrionic and psychopathic disorder. Conclusions: From this level of psychopathological morbidity one can easily deduce that the excessive overexposure to the use of the internet, without a capillary and specific parental control, in childhood and pre-adolescence, exposes the subject to acquire a series of behaviours learned through social-network and more generally on the internet, able to significantly modify the psychophysical growth of the person. If the learned behaviours are then acquired by third parties who manifest dysfunctional behaviours and conducts, because they are in turn the result of psychopathological conditions, the result is the acquisition of that dysfunctional behaviour as 'functional and not pathological', with all the consequences one can imagine. The behavioural mechanism, to simplify, is exactly the same as that of the offence of money laundering: one acquires a dysfunctional and maladaptive behaviour (as is the 'dirty' money in the offence of money laundering) to make it one's own and functional, to obtain one's own psychological benefit (as is the money after being 'cleaned' through the use of operations considered lawful); a psychological benefit that may be the satisfaction of a need, a necessity or a specific requirement (e.g. receiving attention using anger, attracting sexual attention from peers by using provocative attitudes and poses in the presence or through photography or videotaping, or maintaining a certain physical standard because it is socially accepted by using drugs or vomiting or food restriction practices). In view of the alarming results of this research, it seems obvious to provide free psychological support for all families, capable of correcting at an early stage certain dysfunctional behaviours that may have been learnt through unsafe surfing on the Internet, and free support for all young patients who need emotional literacy to correct certain dysfunctions before they take root in their personalities; likewise, it seems obvious to curb the viewing of certain contents which, due to their structure and function, are toxic to the quality of healthy psychophysical growth.